Synthesis of branched and linear galactooligosaccharides related to glucuronoxylomannogalactan of Cryptococcus neoformans - Dorokhova, Vera S.; Komarova, Bozhena S.; Previato, José O.; Mendonça Previato, Lúcia; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2024)
This study focuses on the synthesis of a series of oligo-α-(1→6)-D-galactopyranosides bearing β-D-galactofuranosyl residues at O-2 and/or O-3, which relate structurally to fragments of glucuronoxylomannogalactan (GXMGal) from the fungal pathogen Cryptococcus neoformans that causes severe diseases in immunocompromised patients. The preparation of target compounds is based on the use of a selectively O-protected N-phenyltrifluoroacetimidoyl galactopyranoside donor with an allyl group at O-2, levulinoyl group (Lev) at O-3, pentafluorobenzoyl (PFB) group at O-4, and fluorenylmethoxycarbonyl (Fmoc) group at O-6. The choice of protecting groups for this donor ensures the stereospecific formation of α-(1→6)-glycosidic bonds due to the stereodirecting effect of acyls at O-3, O-4, and O-6. At the same time, this combination of O-substituents permits the selective recovery of free OH groups at O-2, O-3, and O-6 for chain elongation via the introduction of β-D-galactofuranosyl and α-D-galactopyranosyl residues. The reported compounds are obtained as aminopropyl glycosides, which are transformed into biotinylated conjugates for further use as coating antigens in immunological studies. The obtained oligosaccharides were subjected to detailed 13C NMR analysis to show the spatial similarity of the obtained hexasaccharide with the corresponding fragment in the GXMGal chain, making this compound suitable for further immunological studies of C. neoformans.